Sinomenine attenuates uremia vascular calcification by miR-143-5p - Fengyi Yu; Zhong Peng; Ning Gao; Zixu Tang; Zihao Liao; Song Zhao; Shuzhu Zhong; Gloria Umwiza; Hong Huang; Wei Long; Zhangxiu He (Scientific Reports)
Abstract Vascular calcification is considered to be a killer of the cardiovascular system, involved inflammation and immunity. There is no approved therapeutic strategy for the prevention of vascular calcification. Sinomenine exhibited anti-inflammatory and immunosuppressive effects. Objective of this study was to investigate the effect of sinomenine in vascular calcification and its potential molecular mechanism. Adenine-induced uremic rats were constructed and administrated with sinomenine. Optical clearing of aortas, alizarin red staining, von Kossa staining, calcification quantification, micro-CT analyses of vascular calcification were performed to analyze calcification in aortas. Administration of 40 mg/kg/d sinomenine effectively alleviated vascular calcification in uremic rats. The miRNA sequencing revealed differentially expressed miRNAs in aortas and bioinformatic analysis assisted with miRNA screening. We screened 9 differential expressed miRNAs and their predicted target genes. By qRT-PCR, we validated that the expression of rno-miR-143-5p was corresponding to our prediction. Sinomenine inhibited vascular smooth muscle cells (VSMCs) calcification, accompanied with miR-143-5p upregulation. MiR-143-5p mimic decreased VSMCs calcification in high phosphate condition. On the contrary, miR-143-5p inhibitor increased VSMCs calcification in high phosphate condition, which was inhibited by sinomenine. In chronic kidney disease patients with vascular calcification, the expression level of circulating miR-143-5p was lower than those without vascular calcification. Sinomenine significantly inhibited vascular calcification in VSMCs and uremic rat. MiR-143-5p was one of the collection of miRNAs modified by sinomenine in vascular calcification. Reduction of miR-143-5p in VSMCs was not only a concomitant phenomenon in pro-calcification condition but also contribute to VSMCs calcification. Circulating miR-143-5p was supposed to be a potential biomarker for vascular calcification in chronic kidney disease patients. In conclusion, sinomenine effectively alleviated vascular calcification, which was attributed to miR-143-5p regulation partly.